Principles of language learning and teaching - Brown, H. Douglas (Pearson Longman, 2000)
How do people learn a second language? For almost two decades, Principles of Language Learning and Teaching has been recognized as an exceptional guide to the theoretical foundations of language teaching. This new fourth edition offers an overview of the study of Second Language Acquisition, while acting as a reference for the growing storehouse of research, subfields, and specialization of SLA